2010
DOI: 10.3109/08820538.2010.518121
|View full text |Cite
|
Sign up to set email alerts
|

Fundus Autofluorescence in Geographic Atrophy: A Review

Abstract: Fundus autofluorescence is a noninvasive imaging technology that provides information on the distribution of lipofuscin within the retinal pigment epithelial cell monolayer. Progressive accumulation of lipofuscin within retinal pigment epithelial cells is involved in the pathogenesis of geographic atrophy in age-related macular degeneration. This review contains an introduction to fundus autofluorescence, review of currently available imaging methods, and discussion of the role of autofluorescence imaging in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…FAF creates an image using the fluorescent emission from lipofuscin, or the accumulation of granules marking cellular aging and oxidative damage in the RPE [14]. Therefore, due to RPE loss, GA regions in FAF can be represented distinctly by very low image intensity, with clear contrast to the background.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FAF creates an image using the fluorescent emission from lipofuscin, or the accumulation of granules marking cellular aging and oxidative damage in the RPE [14]. Therefore, due to RPE loss, GA regions in FAF can be represented distinctly by very low image intensity, with clear contrast to the background.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, due to RPE loss, GA regions in FAF can be represented distinctly by very low image intensity, with clear contrast to the background. While cases of GA may appear more prominently in FAF, the foveal area also presents with low image intensity and may be confused with GA [14,37]. …”
Section: Introductionmentioning
confidence: 99%
“…Advances in FAF imaging have permitted monitoring of autofluorescence patterns in vivo and have facilitated diagnosis of GA. [14][15][16] Areas of increased FAF are observed at the boundaries of GA lesions and are associated with reductions in both scotopic and photopic retinal sensitivity. [17][18][19] Prospective analysis of FAF patterning in GA patients has demonstrated that new atrophic lesions develop in areas with increased FAF, indicating that increased FAF precedes both development and enlargement of GA lesions.…”
mentioning
confidence: 97%
“…FAF, an in vivo imaging method for metabolic mapping of naturally or pathologically occurring fluorophore of the ocular fundus, has been widely used in the diagnosis of retinal diseases for recent years [7,8]. Lipofuscin precipitate is the main source of autofluorescence.…”
Section: Discussionmentioning
confidence: 99%